2014
DOI: 10.3896/ibra.1.53.5.01
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the activities of Greek and Turkish propolis against Paenibacillus larvae

Abstract: SummaryPropolis has a long history of use in traditional medicine dating back to at least 300 BC, and has been reported to have a broad spectrum of biological activities. Since most studies have to date focused on medical uses of propolis, its antimicrobial activity against honey bee diseases has been little studied. One of the aims of this study was therefore to investigate the potential use of propolis in honey bee health, especially against American foulbrood, which causes much damage in the beekeeping indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 20 publications
3
9
0
Order By: Relevance
“…Numerous studies confirm the antimicrobial activity of propolis of different types against a wide spectrum of microorganisms [ 16 , 26 , 43 , 44 , 66 ]. In fact, the antibacterial activity of propolis is connected with flavonoids and terpenes [ 26 , 37 , 66 ]. For example, flavon apigenin and sesquiterpene alcohol tt -farnesol can inhibit the plaque formation process.…”
Section: Main Biological Propertiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Numerous studies confirm the antimicrobial activity of propolis of different types against a wide spectrum of microorganisms [ 16 , 26 , 43 , 44 , 66 ]. In fact, the antibacterial activity of propolis is connected with flavonoids and terpenes [ 26 , 37 , 66 ]. For example, flavon apigenin and sesquiterpene alcohol tt -farnesol can inhibit the plaque formation process.…”
Section: Main Biological Propertiesmentioning
confidence: 99%
“…The list of biological activities of propolis is very wide. Among them are antiseptic, antibacterial, antimycotic, antiviral, antiprotozoal, antioxidative, spasmolytic, choleric, astringent, anti-inflammatory, anesthetic, antitumor, immunostimulating, cytostatic, hepatoprotective, and other activities [ 4 , 14 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of this study revealed a strong susceptibility of the P. larvae to the tested propolis. [170] Besides, it was revealed that volatiles from Greek propolis also possess antimicrobial activity against human pathogenic agents. [130]…”
Section: Antimicrobial Activity Southern European Coastmentioning
confidence: 99%